2019
DOI: 10.1007/s42729-019-00032-z
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Colonization Promotes the Tolerance to Salt Stress in Lettuce Plants through an Efficient Modification of Ionic Balance

Abstract: Soil salinity is the biggest problem which hinders the productivity of agricultural crops, causing adverse effects on plant growth and development. In this regard, it has been shown that the arbuscular mycorrhizal fungi (AMF) can establish a symbiosis with most agricultural plants improving water and nutrient absorption under salinity stress conditions. The functional contribution of AMF strains (Claroideoglomus claroideum (Cc) and a native consortium of AMF (HM) isolated from saline soils) on the growth and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 39 publications
5
56
0
Order By: Relevance
“…The AMF inoculations were: (1) non‐inoculated (NI) plants; (2) plants inoculated with a consortium containing indigenous ecotypes of AM fungi from Camiña valley (HMC); and (3) plants inoculated with the reference AMF strain Claroideoglomus claroideum (Cc). For each level of AM fungal inoculation, we used three irrigation saline levels: (i) non‐saline irrigation; (ii) plants irrigated with a 40 mmol L –1 NaCl solution; and (iii) plants irrigated with an 80 mmol L –1 NaCl solution, according to previous studies conducted under similar conditions . Two cultivars of lettuce were cropped crossed with the AMF and salinity treatments.…”
Section: Methodsmentioning
confidence: 99%
“…The AMF inoculations were: (1) non‐inoculated (NI) plants; (2) plants inoculated with a consortium containing indigenous ecotypes of AM fungi from Camiña valley (HMC); and (3) plants inoculated with the reference AMF strain Claroideoglomus claroideum (Cc). For each level of AM fungal inoculation, we used three irrigation saline levels: (i) non‐saline irrigation; (ii) plants irrigated with a 40 mmol L –1 NaCl solution; and (iii) plants irrigated with an 80 mmol L –1 NaCl solution, according to previous studies conducted under similar conditions . Two cultivars of lettuce were cropped crossed with the AMF and salinity treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, plant growth, photosynthesis, and nutrient uptake were also improved with AMF inoculation in another woody plant, Zelkova serrata, grown under salt stress (Wang et al 2019). Santander et al (2019) found that AMF inoculation improved ionic balance and prevented the entry of toxic Na + ions into the roots of lettuce under saline conditions. Further, the application of mycorrhizal fungi showed increased plant biomass and phosphorus concentration in turfgrass species under water stress conditions (Aalipour et al 2020).…”
Section: Introductionmentioning
confidence: 95%
“…agricultural ecosystems (Cornejo et al 2017;Anwar et al 2018). AMF are well known as helpful microorganisms which increase plant growth, water stress tolerance, and plant health (Santander et al 2017(Santander et al , 2019. Soil management practices affect not only soil properties and microbial responses but also AMF activities and their plant colonization ability (Cornejo et al 2009; Barea and Pozo 2013;Manoharan et al 2017).…”
Section: Introductionmentioning
confidence: 99%